Influence of molecular structure on the performance of low Voc loss polymer solar cells. Issue 39 (20th September 2016) - Wang, Ming; Wang, Hengbin; Ford, Michael; Yuan, Jianyu; Mai, Cheng-Kang; Fronk, Stephanie; Bazan, Guillermo C.
Abstract : Two regioregular narrow bandgap conjugated polymers (PM1 and PM2) are prepared and their devices exhibit low V oc loss and high short circuit current J sc, but, most significantly, display improved fill factors compared to previously reported PIPCP. Abstract : Two regioregular narrow bandgap conjugated polymers (PM1 and PM2) containing the repeat unit BDT-PT-CPDT-PT (BDT = benzodithiophene, PT = pyridyl[2, 1, 3]thiadiazole, CPDT = cyclopentadithiophene) and different solubilizing alkyl side chains were prepared with the goal of understanding how chemical structure impacts the performance of low V oc loss bulk heterojunction (BHJ) solar cells containing PC61 BM as the acceptor semiconductor. Both polymers show nearly identical orbital energy levels, a face-on orientation relative to the surface normal, and can be processed to yield continuous fiber-like networks in the active layer. Due to the choice of repeat units within the backbone structure, PM1 and PM2 exhibit shorter π–π stacking distances, relative to the previously reported low V oc loss regioregular polymer PIPCP. Finally, PM1 achieves an average PCE of 6.2 ± 0.2% and PM2 achieves an average PCE of 7.2 ± 0.1%. Devices exhibit low V oc loss and high short circuit current J sc, but, most significantly, display improved fill factors compared to previously reported PIPCP. A discussion is provided that seeks to identify structural features in conjugated polymers that lead to devices with low V oc loss and high external quantum efficiencies.